The Motivation of Gen Z Towards Creating a Sustainable Business - Aini, Nurul (Unversitas Muhammadiyah Mataram, 2024)
Abstract: The sustainable business concept considers long-term value between people, the planet, and profit. The idea of sustainable business is considered very urgent amidst massive global climate change. This research aimed to determine Gen Z's motivation to start a sustainable business in the future. The research was conducted with 30 Gen Z from 6 cities in Central Java as respondents. This study uses descriptive analysis with a scoring technique and motivation model using the ERG theory. The research results showed that the motivation of Gen Z in Central Java to create sustainable businesses in the future, especially needs for existence, was very high (average score of 4.38), and for related needs, it was very high (average score of 4.37). For growth, needs were also very high (average score of 4.39). Based on these results, it can be concluded that Gen Z's motivation to create a sustainable business in Central Java was very high, especially in fulfilling primary needs, interaction, and development needs following ERG Theory.